Resemblance, Representation and Scepticism: The Metaphysical Role of Berkeley’s Likeness Principle - David Bartha (Journal of Modern Philosophy)
Berkeley’s likeness principle states that only an idea can be like an idea. In this paper, I argue that the principle should be read as a premise only in a metaphysical argument showing that matter cannot instantiate anything like the sensory properties we perceive. It goes against those interpretations that take it to serve also, if not primarily, an epistemological purpose, featuring in Berkeley’s alleged Representation Argument to the effect that we cannot reach beyond the veil of our ideas. First, in section 1, I raise some concerns about the traditional narrative concerning the likeness principle’s role in Berkeley’s argumentation. In section 2, I delineate an alternative narrative, arguing that there is no ‘missing premise’ in his alleged Representation Argument we need to explain simply because he advances no argument like that in the first place. In section 3–4, I provide a close reading of the relevant passages—first from the Principles, then the Dialogues—and their contexts, supporting textually a purely metaphysical interpretation of the likeness principle arguments. In section 5, I address some possible objections, based on the phrasing of the likeness principle passages and some related texts.